Training induces changes in critical velocity and v4 in age group swimmers - Reis, J.; Alves, F. (Biomechanics and Medicine in Swimming X, 2006)
The aim of this study is to determine the relationships between different methods of assessing aerobic capacity and the changes induced by a heavy aerobic training period in age group swimmers. It was found that critical velocity in front crawl, deter-mined using 50, 200 and 400 meters distances, is similar to velocity correspondent to lactate concentration of 4 mmol.l-1. Critical velocity determined using just 200 and 400 meters distances, however, was significantly different form the former but similar to the mean velocity of the 2000m lest. All variables increased significantly after a 9 weeks aerobic training phase, simultaneously with best performance at 400m front crawl. The results of this study confirm that critical velocity is sensitive to performance changes induced by aerobic training in young swimmers.